Baculovirus Replication Factor LEF-1 Is a DNA Primase - Mikhailov, Victor S. (American Society for Microbiology, 2002)
The baculovirus replication factors LEF-1 and LEF-2 of the Autographa californica multinucleocapsid nucleopolyhedrovirus were overexpressed as fusions containing a hemagglutinin (HA) epitope and a HIS(6) tag using recombinant baculoviruses. LEF-1 was purified to near homogeneity and found to have primase activity in an indirect assay employing Escherichia coli DNA polymerase I (Klenow enzyme) and poly(dT) template. The LEF-1 primase products were also directly characterized by electrophoresis in 20% polyacrylamide-8 M urea gels and agarose gels. Primer synthesis was time dependent, and products of several hundred nucleotides or more were observed from the M13 single-stranded DNA (ssDNA) template. The LEF-1 primase was absolutely dependent on divalent cations (Mg(2+)), and optimal activity was supported by 10 mM MgCl(2). An alkaline pH (8.8 to 9.4) was optimal, whereas monovalent salt (KCl) was inhibitory. Mutation of an invariant aspartic acid in a putative primase domain caused LEF-1 activity to be abolished. Upon ultracentrifugation in glycerol gradients, LEF-1 was found to have a sedimentation coefficient of 3S that is consistent with its being present as a monomer. Elution profiles of LEF-1 and LEF-2 from ssDNA-cellulose and DEAE resin suggested that LEF-2 may bind to both DNA and LEF-1.